Interdigitated Microarray Electrodes Based on Boron-doped Amorphous Carbon for Highly Sensitive Electroanalysis of Redox Analytes Having a Higher Standard Potential - Kensuke HONDA; Shinpei OHTOMO (Electrochemistry)
Interdigitated microarray electrodes were developed based on boron-doped amorphous carbon (B-a-C-IDA) that shows extremely higher overpotential for H2 and O2 evolution. Highly sensitive microanalysis of redox analytes with standard potentials higher than O2 and H2 evolution was achieved by B-a-C-IDA. The amplification of the oxidation current derived from redox cycling was observed at the generator electrode of B-a-C-IDA in the measurement with applying the reduction potential to the collector electrode (dual mode measurement). For Ce3+/4+ with a standard potential of 1.6 V, the amperometric current was amplified 180-fold by applying potentials of 1.7 and 0.8 V to collector and generator electrodes in chronoamperometry (CA) measurement at dual mode. Theoretical detection limit (S/N = 3) for Ce3+ was 0.13 µM. It was two orders of magnitude better than that at B-a-C plate electrode. The factors controlling amplification at B-a-C-IDA with varying gap values were investigated using redox analytes with different types of reactions, diffusion coefficients, and electron transfer rate constants. In addition, the amplification mechanism at B-a-C-IDA electrodes, the contributions of diffusion coefficients, and electron transfer rate constants to the amplification factor were clarified. The method to estimate the amplification factor with diffusion coefficients and electron transfer rate constants when using unmeasured redox analytes was established. The amplification factor when using radioactive analyte UO22+ at B-a-C-IDA with gap size of 2.0 µm was estimated to be 43.2. B-a-C-IDA is expected to enable highly sensitive electroanalysis (low detection limit 0.62 µM).